Síntese de 2-organosselanilbenzo[b]calcogenofenos via ciclização intramolecular de 1-bromo-1-selenoalquenos - Correa, Guilherme Eduardo Stach (2018)
In the present work, two different methodologies were developed for a synthesis of several 2-organylselanylbenzo[b]chalcogenophenes 4a-i from vinyl selenides derived of 1,1-dibromoalkenes 3a-i. In order to obtain the starting materials 3a-1, different 1,1-dribromoalkenes 1a-c were used in the presence of diorganoyl diselenide 2a-c and NaBH4/PEG 400 reductant system, where after 1 hour the desired products were obtained in good yields (74-88%)After the starting materials were obtained, the products 4a-i were obtained by catalysis using CuBr in the presence of CH3NO2 as solvent, argon atmosphere and temperature of 100 °C. Those reactions occurred efficiently and the methodology could be applied to different vinyl selenides containing electron-donating and electron-withdrawing groups substituted in the aromatic ring, where the products were obtained in yields ranged from 60 - 94%Later, when this methodology was already well-founded, a second synthetic route was developed to obtain the same 2- organylselanylbenzo[b]chalcogenophenes 4a, d-g but now using photocatalysis mediated by ultraviolet light in the presence of toluene as a reaction solvent. This methodology was again applied to various vinyl selenides and the desired products were obtained in satisfactory yields in the range of 40 - 90%.